Affective and Cognitive Approaches in Assessing Al-Qur'an Learning: Literature Review - Kholifatin , Luluk Indah; Raihansyah , Muhammad Dafa; Thobroni , Ahmad Yusam (Kamil : Journal of Education, 2025)
This study aims to analyze the impact of affective and cognitive approaches in assessing Qur'anic learning among students. Comprehensive assessment of Qur'anic learning outcomes requires the integration of affective and cognitive aspects. However, in practice, teachers often encounter challenges in implementing such assessments effectively. This study employs a qualitative method using content analysis of various relevant academic sources. The findings indicate that the effective approach enhances students' emotional engagement, motivation, and love for the Qur'an, which in turn fosters their willingness to memorize and understand its content. Meanwhile, the cognitive approach supports pronunciation skills, memorization techniques, and the interpretation of verses. An imbalance between the two approaches may hinder the effectiveness of learning: cognitive dominance without affective engagement reduces motivation, while high affective engagement without cognitive support hampers comprehension. Therefore, integrating both approaches is considered crucial to optimize learning outcomes. Future studies are recommended to examine the effectiveness of such integration through research designs appropriate to the learning context.